Implementation of realistic mathematics education in islamic schools (2018-2022) - Arsyil Waritsman; Dewi Retnowati (12 Waiheru, 2023)
This article was prepared with the aim of systematically and comprehensively investigating articles discussing realistic mathematical approaches applied to mathematics learning in madrasas published from 2018 to 2022. This study uses the systematic literature review method with its stages of identification, screening, eligibility assessment, and inclusion. The results of the investigation were grouped into five major themes in response to the research questions. The findings of this investigation include (1) realistic mathematics education has experienced significant development when applied to mathematics learning in Islamic schools in terms of implementation, effectiveness, and development; (2) realistic mathematics education in Islamic schools has a positive impact on student development in terms of knowledge, attitudes and skills; (3) the research approaches to realistic mathematics approaches applied in Islamic school are quite diverse; (4) the methods used in testing the effectiveness of realistic mathematics education are carried out with pretest-posttest, interviews and questionnaires and (5) the material topics discussed related to research on realistic mathematics education in Islamic school are mostly still on the aspects of numbers and geometry. Overall, the main contribution of this systematic literature review is that a realistic mathematics education applied to mathematics learning in Islamic schools is a positive and promising thing. Furthermore, this study provides additional insight into how a realistic mathematics education is applied to learning mathematics in Islamic schools